The critical role of tissue angiotensin-converting enzyme as revealed by gene targeting in mice. - Esther, C R (1997)
Angiotensin-converting enzyme (ACE) generates the vasoconstrictor angiotensin II, which plays a critical role in maintenance of blood pressure in mammals. Although significant ACE activity is found in plasma, the majority of the enzyme is bound to tissues such as the vascular endothelium. We used targeted homologous recombination to create mice expressing a form of ACE that lacks the COOH-terminal half of the molecule. This modified ACE protein is catalytically active but entirely secreted from cells. Mice that express only this modified ACE have significant plasma ACE activity but no tissue-bound enzyme. These animals have low blood pressure, renal vascular thickening, and a urine concentrating defect. The phenotype is very similar to that of completely ACE-deficient mice previously reported, except that the renal pathology is less severe. These studies strongly support the concept that the tissue-bound ACE is essential to the control of blood pressure and the structure and function of the kidney.